Analisis Pengaruh Kepemimpinan, Komunikasi Dan Motivasi Terhadap Kinerja Pegawai Negeri Sipil Sekretariat Daerah Kebupaten Maybrat - Air, Maximus (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The results of this research showed that the leadership, communication, and motivation, together has an influence to employee performance, which will affect the performance of the organization in this case the performance of the Regional Secretariat Maybrat District. Leadership has an influence on employee performance, which will affect the performance of the organization in this case the performance of the Regional Secretariat Maybrat District. Communication has an influence to employee performance, which will affect the performance of the organization in this case, the performance of the Regional Secretariat Maybrat District. Motivation has an influence the performance of employees that will have an impact on the performance of the organization in this case the performance of the Regional Secretariat Maybrat District. Keywords: Leadership, Communication, Motivation, Performance, Civil Servants